The effect of leverage and liquidity on the value of the firm with age as a moderating variable on companies in Indonesia - Wastam Wahyu Hidayat (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2022)
This study aimed to examine whether there is an effect of leverage and liquidity on the value of the firm with age as moderating variable in companies listed on the Indonesia Stock Exchange in 2019-2021. The sample in the study was 15 companies for 5 years. The data analysis used in this study was carried out quantitatively, with Statistical Product and Service Solutions-23. The results of this study prove that partially leverage has a negative and significant effect on the value of the firm, liquidity ratios have no impact on the value of the firm, age is proven to moderate the leverage ratio to the value of the firm, and age is not proven to mediate the liquidity ratio to the value of the firm. Based on the coefficient of determination that the leverage ratio and the liquidity ratio affect the value of the firm by 81.7%. For comparison, the remaining 18.3% is influenced by other models of variables from.